2011
DOI: 10.1080/02614367.2011.578654
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, power and racism: lifeguards’ influences on Aboriginal people’s experiences at a Northern Canadian aquatic facility

Abstract: Using a Foucauldian and postcolonial lens, this case study examines the ways in which leadership styles used by lifeguards and supported by the structure, rules and regulations at a northern Canadian swimming pool influenced Aboriginal people's experience of the facility. Participant observation, semi-structured interviews and a focus group were used to identify the ways in which Eurocentric lifeguard training, exercises of power, institutional racism and an absence of cultural competency can intersect to infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The findings from this case study suggested that the leadership practices employed by predominantly Euro-Canadian lifeguards from southern Canada had a negative effect on Aboriginal patrons' experiences in the aquatic environment. Rousell and Giles (2011) examined power relations at the pool and determined that lifeguards' approaches to leadership created and proliferated institutionalized racism, which, in turn, created an unwelcoming environment that discouraged Aboriginal patrons from fully participating in pool programs, such as swimming lessons, and from enjoying their experiences at the local pool.…”
Section: Social Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this case study suggested that the leadership practices employed by predominantly Euro-Canadian lifeguards from southern Canada had a negative effect on Aboriginal patrons' experiences in the aquatic environment. Rousell and Giles (2011) examined power relations at the pool and determined that lifeguards' approaches to leadership created and proliferated institutionalized racism, which, in turn, created an unwelcoming environment that discouraged Aboriginal patrons from fully participating in pool programs, such as swimming lessons, and from enjoying their experiences at the local pool.…”
Section: Social Exclusionmentioning
confidence: 99%
“…In Canada's North, Rousell and Giles (2011) examined the ways in which the lifeguards' leadership styles, the structure of programming, and the policies and regulations enforced at a northern swimming facility influenced Aboriginal participants' experiences there. The findings from this case study suggested that the leadership practices employed by predominantly Euro-Canadian lifeguards from southern Canada had a negative effect on Aboriginal patrons' experiences in the aquatic environment.…”
Section: Social Exclusionmentioning
confidence: 99%
“…While there is a significant body of literature concerning the tensions and difficulties of using standardized aquatics programs (i.e., the same program in very different contexts) in Aboriginal communities in Canada's North (Baker & Giles, 2008;Giles, Baker, & Rousell, 2007;Giles, Castleden, & Baker, 2010;Giles, Strachan, Stadig, & Baker, 2010;Rousell & Giles, 2011b), scholars have only begun to discuss the (in)effectiveness of these programs for other ethnic and cultural minority populations (Golob et al, 2013). For example, Giles et al (2007) discussed the lack of culturally appropriate content in standardized aquatics programs for Aboriginal participants in Canada's North (e.g., a failure to accept traditional practices, such as making an offering to the water before heading out in a boat or bringing a gun on a boating excursion, as legitimate) which led to programming that is less meaningful in these contexts.…”
Section: Review Of Literature the Canadian Contextmentioning
confidence: 98%
“…Within an aquatics context, Giles's (2011a, 2011b) research in northern Canada demonstrated the extent to which the organizational culture of an aquatic facility can impact the experiences of participants who do not necessarily share the values of that culture. As the organizational culture in the northern aquatics facility was reflective of the approaches to Eurocentric leadership employed by the mostly Euro-Canadian aquatics staff (Rousell & Giles, 2011a, 2011b and not the often Aboriginal patrons, the authors identified barriers to embracing cultural and JSM Vol. 29, No.…”
Section: Conceptual Framework: Diversity Management In Sport Organizamentioning
confidence: 98%
“…On its website, Right To Play states that 82% of participants believed that they were stronger leaders due to their involvement in the PLAY program (Right To Play 2014). Rose and Giles (2007) and Rousell and Giles (2012), however, pointed out that Eurocentric understandings of leadership do not necessary align with Indigenous understandings of leadership, which can cause problems in leadership programming for Indigenous youth. Right To Play is nevertheless expanding its programs to include urban Indigenous communities (Right To Play 2014).…”
Section: Youth Gender and Sdp For Urban Indigenous Communities In Cmentioning
confidence: 99%